Ethical Challenges for Student Design Projects in Health Care Settings in New Zealand. (23rd September 2018) - Godbold, Rosemary; Lees, Amanda; Reay, Stephen
Abstract: Student‐led design projects undertaken within healthcare settings raise considerable ethical challenges, primarily resulting from collaboration with service users. This article emerged out of the experiences of design from a New Zealand university undertaking real world projects in acute health care contexts. A human‐centred approach to design is underpinned by a requirement for students to immerse themselves in the user context to optimise design outcomes. Several issues exist in relation to the management of the ethical complexities arising from these projects. Multiple formal ethical review processes were triggered when students' projects were defined as research. These processes were perceived as onerous and disproportionate to the scale of the projects, and students were ill equipped to identify ethical issues and engage with formal review processes. This resulted in either abandoned projects or the use of compromised methods. A review of codes of practice and design industry approaches identifies a gap in guidance for both students and qualified designers. Some designers describe their projects as service improvement, and not subject to formal ethical review. This article argues for embedding consideration of ethics in all design projects to enhance the process, to be true to the underpinning philosophy of human centred design and to produce ethically aware graduates. To achieve this, a multi‐pronged pedagogical approach which encompasses both hypothetical, class‐based and real‐world learning experiences is described, with the ultimate goal of normalising the consideration and development of ethical standards for students and best practice across the industry.